2008
DOI: 10.3748/wjg.14.81
|View full text |Cite
|
Sign up to set email alerts
|

Effects of primary suture and fibrin sealant on hemostasis and liver regeneration in an experimental liver injury

Abstract: Out data suggest that fibrin sealant is preferred over primary suture in appropriate cases including liver trauma since it causes less intra-abdominal adhesions while allowing shorter hemostasis time as assessed in experimental liver trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
2
11
0
3
Order By: Relevance
“…This is similar to a study performed on 120 patients with penetrating liver injuries which revealed that firearm injuries tops the list of penetrating trauma patients, constituting 75 % of the total patients [13].…”
Section: Discussionsupporting
confidence: 88%
“…This is similar to a study performed on 120 patients with penetrating liver injuries which revealed that firearm injuries tops the list of penetrating trauma patients, constituting 75 % of the total patients [13].…”
Section: Discussionsupporting
confidence: 88%
“…Fibrin sealants are readily available biological sealants which can be safely used for hemostasis, tissue sealing and engineering [10,19]. Besides, it is a biodegradable product that may stimulate fibroblast growth, and thus decrease the number of adhesions [20].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin sealants (Tisseel, Baxter Biosciences, Vienna, Austria) are biological sealants which can be safely used for hemostasis and tissue sealing [7,10]. In the present study, we aimed to evaluate the effects of fibrin sealant spraying on postoperative air leak in patients undergoing pulmonary resection for non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…Suas propriedades hemostática, oclusiva, adesiva, promotora da cicatrização (estímulo ao crescimento dos fibroblastos) e antisséptica conferem-lhe uma gama de aplicações clínicas 6,17 .…”
Section: Adesivos De Fibrinaunclassified
“…Trabalhos mostram menor intensidade de aderências quando a fibrina é aplicada. Os escores histopatológicos também foram melhores quando comparados com a sutura convencional 6 . Têm sido utilizados em complicações de anastomoses pancreáticas com resultados satisfatórios.…”
Section: Adesivos De Fibrinaunclassified